Analysis of Factors Influencing the Performance of Specialist Doctors at RSI PKU Muhammadiyah Pekajangan - Frans Saputra; Sri Sundari (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
This study aims to analyze the influence of work environment, remuneration, and work motivation on the performance of specialist doctors at RSI PKU Muhammadiyah Pekajangan. This study employed a mixed-methods sequential explanatory design, beginning with a quantitative correlational study of 32 specialist physicians at PKU Muhammadiyah Islamic Hospital in Pekajangan, followed by a qualitative case study with five purposively selected physicians. Work environment, remuneration, work motivation, and performance were measured using a validated and reliable Likert-scale questionnaire; quantitative data were analyzed using descriptive statistics and Pearson correlation, while qualitative data were analyzed using the Miles and Huberman model to deepen the interpretation of the findings. The results of the quantitative analysis showed that the work environment (p = 0.000), remuneration (p = 0.027), and motivation (p = 0.000) significantly influenced the performance of doctors. Qualitative findings revealed that the performance of specialist doctors at RSI PKU Muhammadiyah Pekajangan was influenced by three main factors, namely individual factors (work motivation), organizational factors (remuneration), and work environment factors. Therefore, hospital management is recommended to strengthen a supportive work environment, improve transparency and fairness in the remuneration system, and provide continuous professional development and motivational programs to sustainably enhance specialist physicians' performance. Keywords: Doctor Performance, Work Environment, Remuneration, Work Motivation, Islamic Hospitals